2015
DOI: 10.1111/jpn.12421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with clay‐based binders on biochemical and histopathological changes in organs of turkey fed with aflatoxin‐contaminated diets

Abstract: This study was carried out to investigate the effect of dietary supplementation with molecular or nano-clay binders on biochemical and histopathological examination of organs of turkeys fed diets contaminated with aflatoxin B Two hundred and sixteen unsexed 1-day-old British United Turkeys were randomly allotted to nine diets in a 3 × 3 factorial arrangement of diets supplemented with no toxin binder, molecular toxin binder (MTB) and nano-clay toxin binder, each contaminated with 0, 60 and 110 ppb aflatoxin B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…However, the only enzyme in which a marked increase was observed in the AF+YCW group was the ALT. Lala et al ( 2016 ) reported that ALT levels showed a significant increase in poultry fed with 60 ng AFB 1 /g feed, which is consistent with our findings.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, the only enzyme in which a marked increase was observed in the AF+YCW group was the ALT. Lala et al ( 2016 ) reported that ALT levels showed a significant increase in poultry fed with 60 ng AFB 1 /g feed, which is consistent with our findings.…”
Section: Resultssupporting
confidence: 93%
“…1 b). Previous studies have reported histopathological alterations in the liver of poultry fed with AFB 1 levels ranging from 50 to 1000 ng AFB 1 /g (Giambrone et al 1985 ; Sridhar et al 2015 ; Lala et al 2016 ; Hernández-Ramírez et al 2021 ; Xie et al 2022 ). These alterations include vacuolar degeneration, fatty liver, hemorrhage, congestion, leukocyte infiltration, bile duct hyperplasia, hypertrophy, and portal fibrosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when the AFB 1 produced by the same fungal strain and the animal model was not changed, the doses of different AFB 1 binders that induced the same effect (binding AFB 1 and protecting birds from its toxic effects) varied [31,60,135], probably due to differences in the efficiency of AFB 1 binders. Therefore, a new option consisting of an AF nano-binder has been developed, where adding 2.5 g of nano-clay/kg diet contaminated with 110 μg AFB 1 /kg was more efficient at improving the productivity of turkeys by protecting the liver, kidney, and intestine, as well as for enhancing their functions compared with molecular clay [137,138]. In addition, adding nano-composite magnetic graphene oxide with chitosan (5.0 g/kg diet) decreased the concentration of AFB 1 in the intestine from 18 μg to 6 μg/kg and increased body weight gain and FCR to the levels achieved with an AFB 1 -free diet when chickens consumed a diet contaminated with 22 μg AFB 1 /kg produced by A. parasiticus (FRR 2999) [29].…”
Section: Nutritional Factors For Counteracting Afb1mentioning
confidence: 99%